Beyond the heart: unveiling paroxysmal nocturnal hemoglobinuria in a patient with rheumatic heart disease - Jaine, Nagarjun S.; Purohit, Abhishek; Bohara, Gopal K.; Kaushik, Utkarsh (International Journal of Research in Medical Sciences, 2025)
Paroxysmal nocturnal hemoglobinuria (PNH) is a rare acquired clonal disorder caused by a PIGA gene mutation, leading to glycosylphosphatidylinositol (GPI) anchor deficiency and uncontrolled complement activation. It causes intravascular hemolysis (IVH), thrombosis, and systemic complications. Rheumatic heart disease (RHD), associated with severe valvular pathology, can cause hemolytic anemia. Herein this case reports a 46-year female with RHD-associated aortic stenosis, regurgitation, chronic anemia, jaundice, and hemoglobinuria. Investigations showed hemolysis with elevated lactate dehydrogenase, indirect bilirubin, and reticulocytosis. Chronicity and severity prompted further evaluation. Flow cytometry revealed a significant PNH clone (40.15% in RBCs, >89% in WBCs), confirming complement-mediated hemolysis coexisting with RHD. This case highlights the diagnostic complexity of overlapping hemolytic mechanisms and underscores the importance of considering PNH in unexplained anemia and hemolysis, with early evaluation critical for optimizing outcomes in such rare clinical scenarios.